A comparison of ground and air source heat pump performance for domestic applications: A case study in Perth, Australia. (11th August 2021) - Aprianti, Tine; Tan, Evan; Diu, Chan; Sprivulis, Ben; Ryan, Greg; Srinivasan, Kandadai; Chua, Hui Tong
Summary: This paper aims to assess the efficacy and practical feasibility of implementing a ground source heat pump (GSHP) vis‐à‐vis an air source heat pump (ASHP) for domestic applications. The outcomes of this comparison are based on monitoring each of those systems installed in two near identical adjacent houses in Perth, Western Australia. The former house has an open‐loop groundwater system. There is one family in each house whose operational requirements of the air conditioning system were independent. Data collected from both houses over 2 years was used to determine the cooling capacities delivered and coefficient of performance (COP), as a function of seasonal variations of ambient conditions. It was observed that the COP of the GSHP system was higher than that of the ASHP system for both heating and cooling. Further, these two performance parameters were independent of ambient conditions in the former whereas they show a perceivable ambient dependent trend in the latter. For heating, the GSHP had an average COP of 3.9, independent of outdoor temperatures, while the COP of the ASHP was in a range of 1.9 to 2.9. Likewise, for cooling, the GSHP had an average COP of 3.1 while the COP of the ASHP varied between 1.3 and 2.8. It is concluded that if a borewell is a part of a dwelling, GSHPs result in considerable operating cost savings and a substantial reduction in greenhouse gas emissions. HIGHLIGHTS: Residential ground source heat pump (GSHP) outperforms air source heat pump (ASHP). Immunity of GSHP to ambient temperature variations while heating or cooling. GSHP operates with higher efficiencies. GSHP in tandem with garden bores is economically and environmentally favourable. Abstract : A 2‐year study shows that the coefficient of performance of ground a source heat pump can be up to 100% higher than an air source heat pump in cooling mode and up to 60% in heating mode.